Electric-field-induced on/off switching of the Faraday effect. (17th November 2017) - Hibino, Yuki; Koyama, Tomohiro; Sumi, Satoshi; Awano, Hiroyuki; Miwa, Kazumoto; Ono, Shimpei; Kohda, Makoto; Chiba, Daichi
Abstract: We demonstrate that the Faraday effect can be electrically and reversibly switched on and off at room temperature without changing the external magnetic field. A Co ultrathin film deposited on a Pt underlayer was used for the demonstration. An electric field was applied to the surface of the Co film by forming an electric double layer using an ionic liquid. The switching of the Faraday effect was caused by the electric-field-induced ferromagnetic phase transition in the system. The magnitude of the electrical change in the Faraday rotation angle and the ellipticity are also discussed.